Understanding of polyhydroxybutyrate production under carbon and phosphorus-limited growth conditions in non-axenic continuous culture. (February 2016) - Cavaillé, Laëtitia; Albuquerque, Maria; Grousseau, Estelle; Lepeuple, Anne-Sophie; Uribelarrea, Jean-Louis; Hernandez-Raquet, Guillermina; Paul, Etienne
Highlights: Under C&P limitation, continuous selection of PHB producers was achieved from WAS. A PHB content of 80% was obtained in an open continuous reactor. The nature of the limitation (C, P and dual C&P) depending on D was established. C/P and D governed P-cell content and fraction of C redirected to PHB storage. One-stage but also two-stage continuous processes are proposed for PHB production. Abstract: In a waste into resource strategy, a selection of polyhydroxybutyrate (PHB)-accumulating organisms from activated sludge was achieved in an open continuous culture under acetic acid and phosphorus limitation. Once the microbial population was selected at a dilution rate ( D ), an increase in phosphorus limitation degree was applied in order to study the intracellular phosphorus plasticity of selected bacteria and the resulting capacity to produce PHB. Whatever D, all selected populations were able to produce PHB. At a D, the phosphorus availability determined the phosphorus-cell content which in turn fixed the amount of cell. All the remaining carbon was thus directed toward PHB. By decreasing D, microorganisms adapted more easily to higher phosphorus limitation leading to higher PHB content. A one-stage continuous reactor operated at D  = 0.023 h − 1 gave reliable high PHB productivity with PHB content up to 80%. A two-stage reactor could ensure better productivity while allowing tuning product quality.